Navigating in educational contexts identities and cultures in dialogue - Rajala, Raimo (Rotterdam SensePublishers, 2011)
Navigating in educational contexts: identities and cultures in dialogue includes selected papers from the 2009 Biennial Conference of the International Study Association on Teachers and Teaching (ISATT), held at the University of Lapland in Finland. This volume contains keynote addresses and papers based on the thematic presentations held at the conference: Identity, context and marginality, Professional development and learning, Context and teaching, and ICT in teaching and learning. The articles open perspectives to the challenges in. education and point to the need for dialogue between different racial, cultural, social and gender groups. The articles benefit educators, teacher educators and policy makers aiming to enhance equity and equality. Insights into teachers? professional and personal knowledge are combined with wider social, cultural and global issues, and through experiences of learning both in Real Life and Second Life. There are many inspiring and promising ideas and approaches of how to promote quality teaching and learning. Under network-based education the topics of ICT skills and experiences, models of ICT integration, virtual reality and a simulation-based learning and online tutoring are being described and assessed. The book is rooted in the studies, practises and arguments of researchers, teachers, educators and students navigating in diverse educational contexts. It will fascinate all those involved and interested in challenging educational practises and thinking.
Electronic reproduction .
Keywords: Teachers -- training of; Teaching; Education -- study and teaching; Electronic books